2020
DOI: 10.1109/jetcas.2020.2970077
|View full text |Cite
|
Sign up to set email alerts
|

Error Analysis of Programmable Metasurfaces for Beam Steering

Abstract: Recent years have seen the emergence of programmable metasurfaces, where the user can modify the EM response of the device via software. Adding reconfigurability to the already powerful EM capabilities of metasurfaces opens the door to novel cyber-physical systems with exciting applications in domains such as holography, cloaking, or wireless communications. This paradigm shift, however, comes with a non-trivial increase of the complexity of the metasurfaces that will pose new reliability challenges stemming f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 64 publications
(80 reference statements)
4
37
0
Order By: Relevance
“…It is important to state that, the numbers can vary depending on the dimension of MSF and configuration of NNs, but the order of magnitude will remain similar. Moreover, this has been corroborated by multiple studies such as [ 40 , 41 , 42 ]. For a more in-depth analysis into the computational complexity of NNs, analytical methods, and full-wave simulators, we refer the reader to Appendix B .…”
Section: Introductionsupporting
confidence: 65%
“…It is important to state that, the numbers can vary depending on the dimension of MSF and configuration of NNs, but the order of magnitude will remain similar. Moreover, this has been corroborated by multiple studies such as [ 40 , 41 , 42 ]. For a more in-depth analysis into the computational complexity of NNs, analytical methods, and full-wave simulators, we refer the reader to Appendix B .…”
Section: Introductionsupporting
confidence: 65%
“…Several research papers on the design of software-defined metamaterials and nano-communication networks for application to metasurfaces have recently appeared in the literature. The research issues tacked in these papers encompass the definition of softwaredefined primitives, the analysis of communication and security issues, the design of medium access control protocols, routing protocols, and the network layer configuration and operation [259], [260], [261], [262], [263], [264], [265]. Interested readers are referred to [56] for further information.…”
Section: S Software Defined Networking Based Design and Nano-communimentioning
confidence: 99%
“…9 which depicts unreachable node sums (i.e., faulty, victimized and FB boundary) as a function of faulty node counts, for the RF and CF scenarios 3 . It is observed that at an average 1.6% total faulty nodes, 66% and 76% of all nodes are spanned by the proposed FT algorithm under the respective RF and CF scenarios; these values constitute acceptable HSF functionality that is tolerant to some directives loss [12]. Moreover, Fig.…”
Section: Hsf Ft Routing: Turns Employed and Prohibitedmentioning
confidence: 88%
“…Such HSFs must safeguard against faults during fabrication, deployment, or operation, which have been shown to degrade HSF performance and are caused by factors such as connector misalignment, ageing, physical or intentional damage of unit cells, etc. [12]. As such, to establish dependable communication among interconnected controllers in an HSF structure, we propose a link-level Fault-Tolerant (FT) routing algorithm that arms routed packetized directives 1 , that reconfigure EM properties of meta-atoms in the HSF, in bypassing faulty nodes on their way to their destination controllers.…”
Section: Introductionmentioning
confidence: 99%